The neolithic-eneolithic sequence and pottery assemblages in the fifth millennium BC in north-eastern Slovenia - Kramberger, Bine (Documenta Praehistorica, 2014)
This paper discusses the settlements at Andrenci, Stoperce, Ptuj-Šolski center, Zgornje Radvanje and Hoče-Orglarska delavnica, all located in north-eastern Slovenia. The settlements are dated on the basis of the results of radiocarbon analyses. The characteristics of the material and cultural-chronological site structures were studied through analyses of pottery (pottery production, form, decoration) and comparative analyses.
Keywords: ceramic; datiranje; eneolitik; keramika; lončevina; naselja; neolitik; prazgodovina; severovzhodna Slovenija